NON-PHARMACOLOGICAL INTERVENTION TO EASY LABOR: LITERATURE REVIEW - Sukmawati, Sukmawati; Mamuroh, Lilis; Nurhakim, Furkon (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2025)
The labor process involves physical and psychological mechanisms. The labor process does not always run smoothly and often encounters various obstacles that can cause various problems and even result in the death of the mother or fetus. The right method to facilitate labor is needed with the consideration that the method chosen is safe for the mother and baby. The purpose of this study was to determine non-pharmacological interventions that can be used to facilitate labor.. The research method used Scoping Review, ScienceDirect, Scopus, Proquest, Ebsco, and Pubmed article search databases. Inclusion criteria were experimental or cohort studies, published in 2014–2024, full-text articles, pregnant women stage I population, and independent variables of non-pharmacological interventions to facilitate labor. The keywords used in English were “Pregnant women” OR “Pregnant mother”, “Nursing intervention” OR “Non-Pharmacology”, “Labor”. Study quality was assessed using the Joanna Briggs Institute (JBI). From the results of the research selection of 671 articles, 11 articles met the inclusion criteria and eligibility for analysis. All research results showed that non-pharmacological interventions can be used by pregnant women to facilitate labor, namely consuming 7 packs of dates, Swiss ball exercises, lumbosacral massage, warm water baths, PFME, Kaiser physical activity, pilates exercises, pelvic rocking exercises, TENS therapy, consuming 7 dates, date juice, yoga. Non-pharmacological therapy can facilitate labor by reducing anxiety levels and reducing pain intensity.This literature review highlights the benefits of non-pharmacological therapy during pregnancy to facilitate labor. Non-pharmacological therapy is needed to facilitate labor.